The Impact of Borrowing and Lending Account Growth on The Profitability of Fintech Lending Companies - Puspitasari, Nabila Cahita; Achsani, Noer Azam; Irawan, Tony (Business Review and Case Studies, 2024)
Background: Fintech lending or online lending services is one of the innovations in the financial industry that is growing rapidly and has a significant impact on the economy in Indonesia, especially for MSMEs. The increase in outstanding online loans in Indonesia is because online loan services are considered easier to apply for than traditional financial services. Purpose: This study analyzes the impact of increasing borrower and lender accounts, bad loan risk, and macroeconomic conditions on the profitability of fintech lending companies in Indonesia over the past five years.Design/methodology/approach: This study uses monthly time series data with a research period from January 2019 to December 2023. The type of data used in this study is secondary data obtained from the official websites of Bank Indonesia, OJK, and S&P Global. This study uses the Autoregressive Distributed Lag (ARDL) analysis method using E-views12 software.Findings/Results: The results show that the firm's profitability tends to increase in the short run when the number of lender accounts increases. At the same time, the non-performing loans, inflation, and interest rates decrease. In the long run, borrower account growth, lender account growth, and Purchasing Manager's Index (PMI) positively affect the profitability of fintech lending companies. The growth of Fintech Lending in Indonesia has experienced rapid growth in the past 5 years, especially in the period 2021-2022. The outstanding online loans increased dramatically due to the COVID-19 pandemic. The development of borrower and lender accounts can positively impact company profitability but also increase the risk of bad loans.Keywords: Fintech Lending, Return on Assets (ROA), Non-Performing Loan (NPL), Purchasing Manager’s Index (PMI), Autoregressive Distributed Lag (ARDL)